2002
DOI: 10.1097/00007632-200205010-00022
|View full text |Cite
|
Sign up to set email alerts
|

Helmet and Shoulder Pad Removal in Suspected Cervical Spine Injury

Abstract: In the conscious player with no cervical injury the protocol used by the NATA is effective in limiting cervical motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…11,12,19 Most of the research in this area has been performed using football or hockey equipment. Previous cadaver research 11 using fluoroscopy demonstrated that flexion occurs during football helmet removal in uninjured (5.56) and unstable (9.36) cervical spines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,12,19 Most of the research in this area has been performed using football or hockey equipment. Previous cadaver research 11 using fluoroscopy demonstrated that flexion occurs during football helmet removal in uninjured (5.56) and unstable (9.36) cervical spines.…”
Section: Discussionmentioning
confidence: 99%
“…Significant findings 25 of alterations in the position of adjacent cervical vertebrae have been noted during helmet removal, cervical collar application, and head rest using fluoroscopy in participants wearing hockey and football equipment. Researchers 11,12,25 have also noted that helmet removal resulted in increased cervical traction, which may be harmful in the unstable cervical spine. In research involving human controls, investigators 12 noted no changes in the angulation, disc height, or SAC in the uninjured cervical spine with helmet removal when following the National Athletic Trainers' Association protocol for helmet removal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that removing the helmet may be the best treatment plan until a helmet that properly stabilizes the head can be designed. Peris et al 12 and Prinsen et al 13 investigated motion that occurs during helmet and shoulder pad removal. Peris et al 12 noted that when the IATF 5 guidelines were followed, no significant motion occurred when removing the helmet and shoulder pads.…”
Section: Helmet Fittingmentioning
confidence: 99%